Managing the risks of extreme events and disasters to advance climate change adaptation : special report of the Intergovernmental Panel on Climate Change - Field, Christopher B. (Cambridge University Press, 2012)
Extreme weather and climate events, interacting with exposed and vulnerable human and natural systems, can lead to disasters. This Special Report explores the social as well as physical dimensions of weather- and climate-related disasters, considering opportunities for managing risks at local to international scales. SREX was approved and accepted by the Intergovernmental Panel on Climate Change (IPCC) on 18 November 2011 in Kampala, Uganda.